ANALISA KAPASITAS KEUANGAN PEMERINTAH DAERAH DAN KESINAMBUNGAN PENYELENGGARAAN LAYANAN PUBLIK - Picicia, Nora; Wahidin; Wahyunadi (Jurnal Ilmu Ekonomi, 2023)
Regional Government Financial Capacity is the finansial capacity of each region in managing the planned programs. The implementation of region finance in knowing the description of regional financial management is carried out through an analysis of the implementation of the APBD. Therefore, the implementation of Public Services by Regional Governments by providing facilities or infrastructure is financed from the Capital Expenditure budget allocation. The purpose of this study is analyze to what extent the financial capacity/ability of the Regional Government in optimizing its revenue from the Regional Original Revenue (PAD) and Balancing Funds to maintain the continuity of the implementation of Public Services through the allocation of Capital Expenditures to Regencies/Cities in the Province of NTB. This type of research is include in quantitative research with an associative strategy. The research technique was carried out by searching secondary data which was processed using a computer, namely Eviews 12. The results of the study show that PAD (X1) has no significant effect on Public Services through Capital Expenditures (Y), Balancing Funds (X2) hasa significant effect on Public Service Through Capital Expenditure (Y), and together PAD (X1) and Balance Fund (X2) has a positive and significant effect on Public Services through Capital Expenditures (Y) in the Regencies/Cities of the NTB Province.